Conceptual exploration of power peak shaving by smart train operation in rail freight transport. (August 2022) - Liu, Zhendong; Berg, Mats; Ekmark, Anders
Powerful electric locomotives with high traction performance are foreseen to be used to boost the overall performance of freight transport. However, they would exert extra burden on the power supply system, so the power peak demand would be a bottleneck for future freight transport. To avoid large-scale modifications to the existing systems but ensure operational reliability, this study investigates the formation of power peaks and explores power peak shaving concepts to let the existing systems be more reliable and accommodate more freight traffic. Different from many previous studies which focus on energy saving, this study aims at lowering the power peak demand by "smart train operation", i.e. altering the train speed profile without compromising running time. This study is mainly performed by simulation based on a standardized freight operation with full regenerative braking used. But this study also shows a real case study based on measurement data of power history from an onboard energy meter. The study shows the formation of power peaks in different conditions and suggests some possible measures to shave the power peak demand. The study also shows that there is a compromise between power peak shaving and energy saving, to which more attention is needed in future studies.